2020
DOI: 10.3390/ijerph17145102
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Threat of COVID-19 Contagion and Frontline Paramedics’ Agonistic Behaviour: Employing a Stressor–Strain–Outcome Perspective

Abstract: Historically, infectious diseases have been the leading cause of human psychosomatic strain and death tolls. This research investigated the recent threat of COVID-19 contagion, especially its impact among frontline paramedics treating patients with COVID-19, and their perception of self-infection, which ultimately increases their agonistic behaviour. Based on the stressor–strain–outcome paradigm, a research model was proposed and investigated using survey-based data through a structured questionnaire. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 102 publications
(155 reference statements)
3
49
0
6
Order By: Relevance
“…Direct contact with COVID-19 patients was associated with poor mental health outcomes, 8,13,31,35,36,43,45,46,47,48 as well as personal fear of infection and perceived threat of contagion. 13,21,22,27,32,37,49,50,51 These adverse outcomes were also seen in HCWs with friends or family with COVID-19 infection 22,32,33,34,49 and in HCWs with colleagues who were hospitalized or died of COVID-19. 39 Further, working in COVID-19 designated hospitals compared to non-designated hospitals 25,49,52 and working in COVID-19 specific isolation wards 13,22,40,45 were associated with poorer mental health outcomes.…”
Section: Resultsmentioning
confidence: 91%
“…Direct contact with COVID-19 patients was associated with poor mental health outcomes, 8,13,31,35,36,43,45,46,47,48 as well as personal fear of infection and perceived threat of contagion. 13,21,22,27,32,37,49,50,51 These adverse outcomes were also seen in HCWs with friends or family with COVID-19 infection 22,32,33,34,49 and in HCWs with colleagues who were hospitalized or died of COVID-19. 39 Further, working in COVID-19 designated hospitals compared to non-designated hospitals 25,49,52 and working in COVID-19 specific isolation wards 13,22,40,45 were associated with poorer mental health outcomes.…”
Section: Resultsmentioning
confidence: 91%
“…These studies indicate that threat orientation impacts how an individual responds to a fear appeal. 43 Thus, we hypothesize the following:…”
Section: Perceived Threat and Fear Arousalmentioning
confidence: 99%
“…Perceived efficacy is also an important determinant of the fear aroused by the threat of a disease, ie, ability to control fear increases as perceived efficacy increases. 43,44 An empirical study by Shi & Smith 4 found that people engage in danger control processes (ie, fear control processes) when they perceive that their selfefficacy is higher than the threat. Thus, we propose the following hypothesis:…”
Section: Perceived Efficacy and Fear Arousalmentioning
confidence: 99%
“…This includes nurses taking care of COVID-19 patients at the scenes of COVID-19 contaminations, where they must wear protective equipment for long hours, leaving marks on their faces [ 4 ]. However, as COVID-19 has been continuing interminably, health care workers are encountering hardships in carrying out their jobs [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%